2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20181830
|View full text |Cite
|
Sign up to set email alerts
|

Intense pulsed light for the treatment of hirsutism

Abstract: <p class="abstract"><strong>Background:</strong> Hirsutism can represent a severe cosmetic disturbance, sometimes with psychological implications. Various lasers and broadband light sources have been developed for treatment of hirsutism. The objective of this study was to know the efficacy of IPL in hirsutism patients</p><p class="abstract"><strong>Methods:</strong> Forty patients were included in the study. Treatment parameters in respect of pulse duration and fluence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…Of course, satisfaction varies from one person to another. However, our study found that 71% of patients expressed satisfied, and 25.8% were very satisfied which is nearly similar to the study of Subha et al [14].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Of course, satisfaction varies from one person to another. However, our study found that 71% of patients expressed satisfied, and 25.8% were very satisfied which is nearly similar to the study of Subha et al [14].…”
Section: Discussionsupporting
confidence: 90%
“…But it is so higher in Iraqi ladies where the facial hirsutism affects 26.8% of them [13]. The response to IPL treatment for facial hirsutism varies from 10 to 88.66% among various researchers [1,6,11,12,[14][15][16][17][18][19][20][21]. The current study showed that 62.9% had good and 25.8% excellent hair reduction rate.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The discovery of novel economic and safe methods for treatment of hirsutism is of great importance as the notable cost of routinemethods such as electrolysis and photo-epilation and serious side effects of oral hormonal therapies such as anti-androgenic agents. [16][17][18] In our study, side effects such as local inflammation, edema, or scaling of skin from topical acyclovir were not observed, therefore this drug can be suggested as a new topical agent for decreasing hair growth in hirsutism. However, further studies should be performed to confirm this hypothesis and additional clinical research is required to further determine the potential of acyclovir as a pharmacologic strategy for hirsutism.…”
Section: Discussionmentioning
confidence: 82%